2018
DOI: 10.1016/j.jcjo.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral retinitis pigmentosa: clinical and electrophysiological diagnosis

Abstract: To conclude, URP is an uncommon entity, with fewer than 100 cases reported in the literature. 7 Therefore, clinical signs and symptoms, a minimum of a 5-year follow-up period, and confirmatory ERG and visual field testing are very helpful in elucidating the unilateral pattern of the disease and in monitoring these individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
(14 reference statements)
0
2
0
2
Order By: Relevance
“…While it has been suggested that all of these criteria are necessary to diagnose URP [ 15 ], the 5-year follow-up duration to diagnose URP today seems to be an unnecessarily long follow-up period in the era of advanced molecular genetic testing. In patient 2 the ffERG was affected in both eyes, demonstrating a bilateral retinal dystrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it has been suggested that all of these criteria are necessary to diagnose URP [ 15 ], the 5-year follow-up duration to diagnose URP today seems to be an unnecessarily long follow-up period in the era of advanced molecular genetic testing. In patient 2 the ffERG was affected in both eyes, demonstrating a bilateral retinal dystrophy.…”
Section: Discussionmentioning
confidence: 99%
“…The AGBL5 (ATP/GTP-binding like protein) gene has recently been found to cause autosomal recessive non-syndromic retinitis pigmentosa (arRP) [ 15 , 16 , 17 ]. AGBL5 is a member of the cytosolic carboxypeptidase (CCP) protein family; members of this family are involved in post-translational modification (PTMs) of a- and b-tubulin, which are the main constituents of microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…Outros padrões de perda também existem como: perda de campo visual concêntrica sem formação de anéis de escotomas e perda de campo em padrão arqueado. Ademais, fotofobia e discromatopsia também fazem parte do espectro de manifestações clínicas, sendo esta última mais comum em estágios avançados, principalmente os defeitos visuais da cor azul (Verbakel et al, 2018 (Bhattarai et al, 2015;Stamate et al, 2016;Mercado et al, 2018;Bawankar et al, 2018;Errera et al, 2019). Fonte: (Bhattarai et al, 2015;Stamate et al, 2016;Mercado et al, 2018;Bawankar et al, 2018;Errera et al, 2019).…”
Section: Quadro Clínicounclassified
“…Todavia deve-se atentar a algumas patologias que podem causar uma retinopatia degenerativa semelhante à RPU, constituindo diagnósticos diferenciais, como: doenças infecciosas (rubéola congênita, toxoplasmose, sífilis), neoplásicas, inflamatórias (vasculites retinianas), trauma (corpo estranho intraocular, trauma contuso) e toxicidade por drogas (cloroquina/hidroxicloroquina, fenotiazinas) (Stamate et al, 2016;Mercado et al, 2018;Bawankar et al, 2018).…”
Section: Critérios De François E Verriest (1952)unclassified